HEALTH IMPLICATIONS OF COMPETITIVE ESPORTS: A SYSTEMATIC REVIEW OF PHYSICAL, MENTAL AND SOCIOBEHAVIORAL OUTCOMES - Kamil Turlej; Anastazja Orłowa; Aleksandra Oparcik; Kinga Szyszka; Klaudia Martyna Patrzykąt; Marta Cieślak; Anita Pakuła; Anna Baranowska; Laura Kurczoba; Julia Pawłowska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Competitive electronic sports (esports) represent a rapidly expanding global discipline with distinctive training loads and lifestyle patterns. While esports provide opportunities for performance development and social connectedness, they also raise concerns regarding musculoskeletal strain, sleep disruption, sedentary cardiometabolic risk, mental-health burden, and the use of cognitive enhancers. Objective: To systematically synthesize evidence from last decade on physical, psychological, and sociobehavioral health outcomes associated with competitive esports participation, and to evaluate implications for clinical practice, athlete welfare, and public-health policy. Methods: We will search PubMed/PMC, Scopus, Embase and Web of Science. Eligible studies include observational research, randomized trials, systematic reviews, and position statements assessing health outcomes in competitive gamers or comparing esports athletes with controls. Outcomes include musculoskeletal symptoms, sleep and circadian patterns, mental health (depression, anxiety, stress, problematic gaming), cardiometabolic markers and sedentary behavior, visual strain, and stimulant/nootropic use. A meta-analysis or narrative synthesis will be performed where appropriate, with subgroup analyses by age, competitive level, and game genre. Results: Evidence consistently shows high rates of musculoskeletal complaints, sleep irregularities, and sedentary behavior among professional eAthletes. Studies also report mixed cardiometabolic findings, mental-health vulnerabilities, and emerging concerns regarding performance-enhancing stimulant or nootropic use. Heterogeneity in study methods and definitions limits data pooling but identifies priority areas for prevention. Conclusions: Overall, competitive esports are associated with a multifaceted health profile encompassing physical, psychological, and lifestyle domains. Standardized methodologies, longitudinal monitoring, and structured pre-participation screening are needed to inform evidence-based guidelines and improve athlete safety across clinical, public-health, and governance settings.